Examination of program exposure across intervention delivery modes: face-to-face versus internet - Mummery W Kerry; Steele Rebekah M; Dwyer Trudy (BMC, 2007)
Abstract Background There has been increasing interest in the ability of the internet to produce behaviour change. The focus of this study was to describe program exposure across three intervention groups from a randomised trial (RT) comparing traditional face-to-face, internet-mediated (combined internet plus face-to-face), and internet-only program delivery. Methods Baseline and immediately post-intervention survey data, and exposure rates from participants that commenced the RT were included (n = 192). Exposure was defined as either face-to-face attendance, website usage, or a combination of both for the internet-mediated group. Characteristics of participants who were exposed to at least 75% of the program material were explored. Descriptive analysis and logistical regression were used to examine differences between groups for program exposure. Results All groups showed decrease in program exposure over time. Differences were also observed (χ2 = 10.37, p < 0.05), between intervention groups. The internet-mediated (OR = 2.4, 95% CI 1.13-5.1) and internet-only (OR = 2.96, 95% CI 1.38-6.3) groups were more likely to have been exposed to at least 75% of the program compared to the face-to-face group. Participants with high physical activity self-efficacy were 1.82 (95% CI 1.15-2.88) times more likely to have been exposed to 75% of the program, and those allocated to the face-to-face group were less likely to have attended 75% of the face-to-face sessions if they were classified as obese (OR = 0.21 95% CI 0.04-0.96). Conclusion These results suggest that the internet groups were as effective as the face-to-face delivery mode in engaging participants in the program material. However, different delivery methods may be more useful to different sub-populations. It is important to explore which target groups that internet-based programs are best suited, in order to increase their impact.